The regional distribution of income and wages: Causes and consequences - Lea Immel (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2021)
Lea Immel prepared this study while she was working at the Research Group Taxation and Fiscal Policy at the ifo Institute. The study was completed in September 2020 and accepted as doctoral thesis by the Department of Economics at the University of Munich. It consists of four distinct empirical essays investigating the causes and consequences of regional di erences in the distribution of income and wages using county-level data from Germany. Chapter 2 analyzes the impact of the so-called Hartz reforms on income inequality in German regions. Chapter 3 investigates the long-term effect of university openings on the wage distribution in the surrounding area. Chapters 4 and 5 turn to the political consequences of regional income dispersion and examine the effect of relative economic deprivation on the support for radical right- and left-wing parties as well as on local fiscal policy. The chapters employ difference-in-differences, event study, and instrumental variable estimations to answer the respective research questions.
Keywords: D31; D73; H41; H71; H72; I23; I25; I32; J08; J31; J68; R23; R58; 330; Labor market policy; income inequality; wages; Germany; Hartz reforms; universities; knowledge spillovers; local labor markets; economic deprivation; political polarization; radical voting; poverty; taxation; fiscal policy; public services; difference-in-differences; event study; instrumental variables